Working Capital Management dan Firm Profitability Perusahaan Sektor Manufaktur di Bursa Efek Indonesia dan Bursa Efek Filipina Periode 2014-2018 - Ricky Adiyanto; Werner Ria Murhadi; Liliana Inggrit Wijaya (Journal of Entrepreneurship and Business, 2020)
This study aims to analyze the effect of working capital management on the profitability of companies in Indonesia and Philippines. This study uses secondary data from companies listed in Indonesia Stock Exchange and Philippines Stock Exchange in the 2014-2018 period. The sample used in this study includes manufacturing sector companies listed in Indonesia Stock Exchange and Philippines Stock Exchange in that period. This research uses multiple linear regression method. Working capital is measured using cash conversion cycle, accounts receivable conversion period, inventories conversion period, and accounts payable deferral period. The results of the Indonesian sample show that the cash conversion cycle and its components, namely the accounts receivable conversion period, the inventories conversion period, and the accounts payable deferral period have a significant positive effect on firm profitability. For the Philippine sample, the result of the study show that the cash conversion cycle and its components does not have a significant effect on firm profitability. Keywords: cash conversion cycle, accounts receivable conversion period, inventories conversion period, accounts payable deferral period